2017
DOI: 10.14814/phy2.13467
|View full text |Cite
|
Sign up to set email alerts
|

Oral and intravenous pharmacokinetics of taurine in sprague-dawley rats: the influence of dose and the possible involvement of the proton-coupled amino acid transporter, PAT1, in oral taurine absorption

Abstract: Taurine is involved in various physiological processes, and one of the most abundant amino acids in human. The aim was to investigate the mechanism for intestinal absorption of taurine in vivo using also in vitro mechanistic studies. Taurine absorption was measured in male Sprague‐Dawley rats at 10–997 mg/kg and 1–30 mg/kg for oral and intravenous administration, respectively. Oral absorption was measured in the presence of substrates for the proton‐coupled amino acid transporter, PAT1, that is, 200 mg/kg prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
(74 reference statements)
0
14
0
1
Order By: Relevance
“…Taurine was found in all blue whiting protein containing diets, with the highest amounts in the hydrolysate diets; however, we observed no direct association between plasma taurine concentration and blood pressure development. The plasma elimination half-life for taurine after oral intake is estimated to be < 2 h in both rats and humans [ 70 , 71 ], and since our rats were fasted for 12 h before blood sampling, the lack of association between dietary taurine intake and plasma concentration of taurine can most likely be explained by the rapid turnover of taurine. The higher dietary intake of taurine in rats fed blue whiting protein diets may be among the nutrients contributing to the lower blood pressure increase in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine was found in all blue whiting protein containing diets, with the highest amounts in the hydrolysate diets; however, we observed no direct association between plasma taurine concentration and blood pressure development. The plasma elimination half-life for taurine after oral intake is estimated to be < 2 h in both rats and humans [ 70 , 71 ], and since our rats were fasted for 12 h before blood sampling, the lack of association between dietary taurine intake and plasma concentration of taurine can most likely be explained by the rapid turnover of taurine. The higher dietary intake of taurine in rats fed blue whiting protein diets may be among the nutrients contributing to the lower blood pressure increase in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…The body taurine pool is composed of dietary taurine absorbed in the gastrointestinal tract (GIT) and endogenous taurine synthesized in the liver. Two different solute carrier proteins for intestinal taurine transport have been characterized in mammals: the high‐capacity proton/amino acid symporter (PAT1) and the low‐capacity taurine transporter (TAUT) . Anderson et al .…”
Section: Introduction To Taurinementioning
confidence: 99%
“…2 PAT1 being a high capacity amino acid transporter with low affinity, it was unlikely to be saturated even at very high taurine concentrations. 2 Furthermore, support to the role of PAT1 was obtained from the in vivo pharmacokinetic study of taurine in rats; the saturation in absorption was not observed despite the use of large oral doses of taurine (10 to 997 mg/kg). 2 From the above, it can be deduced that the dose of 6 g/day of taurine would not saturate the absorption process because of its high intestinal absorptive capacity.…”
Section: Editorsmentioning
confidence: 93%